THE MIXING PROPERTIES OF MELTS AND GLASSES IN THE SYSTEM NAALSI3O8-KALSI3O8 - COMPARISON OF EXPERIMENTAL-DATA OBTAINED BY KNUDSEN CELL MASS-SPECTROMETRY AND SOLUTION CALORIMETRY - Fraser, D; Bottinga, Y (1985)
The apparent differences between heats of mixing determined by solution calorimetric measurements on quenched samples in the system NaAlSi3O8-KAlSi3O8 and heats of mixing determined at high temperatures by Knudsen cell mass spectrometry are caused by thermal effects related to the glass transition. When these effects are allowed for, the calorimetric data and Knudsen cell measurements are in good agreement. © 1985.